Challenges and opportunities of artificial intelligence in education in a global context - Silva, Altieres de Oliveira; Janes, Diego dos Santos (Review of Artificial Intelligence in Education, 2023)
Objective: The objective of "Generative AI and the Future of Education" by Stefania Giannini at UNESCO is to examine the transformative impact of generative artificial intelligence (AI) on the educational sector, focusing on the implications for teaching, learning, and knowledge dissemination. Method: The document employs a qualitative analysis, drawing on existing literature, case studies, and theoretical frameworks to explore the integration of AI technologies in education. It addresses the challenges and opportunities presented by AI, emphasizing the need for a balanced approach to its adoption in educational settings. Results: Giannini identifies several key areas where AI has the potential to revolutionize education, including personalized learning, accessibility, and the democratization of knowledge. However, the document also highlights significant challenges, such as ethical concerns, the digital divide, and the need for adequate regulatory frameworks to ensure equitable and safe use of AI in education. Practical Implications and Conclusions: The document advocates for the development of comprehensive strategies to harness the potential of AI in education responsibly. It calls for international collaboration among policymakers, educators, and technologists to create inclusive, equitable, and human-centered educational systems. Giannini concludes that with thoughtful integration, AI can enhance educational outcomes, but emphasizes the importance of maintaining a focus on human values and critical thinking skills.